HOW THE GOVERNMENT REGULATES CODE SWITCHING ADVERTISEMENTS MADE BY MSME AS A PUBLIC INFORMATION: A CRITICAL DISCOURSE ANALYSIS - Edwar Kemal; Suhaida Omar (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Since Indonesia join for ASEAN Economic Community (AEC) by the end of 2015, English has been playing a vital role for the economics growth. MSMEs, especially Micro Enterprises, have been supported by the government to grow and develop the economics. One of the ways for the MSMEs to do so is by promoting and selling their product and service towards code switching Advertisement. To facilitate the right and obligation between the MSMEs as the advertiser, and the customers, as the product and service users, the Indonesian Government issues an Advertisement regulation. This research aims to find out how the regulation of the advertisement is and how the MSMEs implement it on their advertisement. This research was a qualitative research using a case study design. Data of the research were collected towards document checklist. There were 10 advertisements as research data from the type of food and service business. Data were analyzed by using content analysis towards Fairclough’s Critical Discourse Analysis. The research shows that from the structure of the text, it is seen that most of the Micro MSMEs on making the advertisement have followed the structure of the text of advertisement. However, related to the information of each part, it is found that there are two violations found on the advertisement such ignorance of the equivalences on the orientation (name of trademark) and on the body of the advertisement containing the product or service offered. The English used has been wrong in lexical and diction.